Candida auris Biofilm Colonization on Skin Niche Conditions - Priya Uppuluri (American Society for Microbiology, 2020)
ABSTRACT Candida auris, an emerging multidrug-resistant yeast, has recently been associated with outbreaks of invasive infections in health care facilities worldwide. Its success as a nosocomial pathogen lies in its capability to sustain for prolonged periods in the intensive care unit (ICU), adeptly colonize skin, and spread among patients. Little is known of the mechanism behind the predilection of C. auris for skin or the extent of its resilience on it. Now, M. V. Horton, C. J. Johnson, J. F. Kernien, T. D. Patel, et al. (mSphere 5:e00910-19, 2020, https://doi.org/10.1128/mSphere.00910-19) demonstrate that in synthetic sweat medium designed to mimic axillary skin conditions, C. auris can grow into multilayers of cells called biofilms that can resist desiccation. C. auris’ propensity to form biofilms was further elaborated using a novel ex vivo porcine skin model of skin colonization. These studies provide early evidence that C. auris biofilm cells persisting on skin could serve as source of continuing outbreaks in health care facilities. Interventions blocking C. auris biofilm growth on skin will help control the spread of this pathogen.